Magic and Memory: Dido's Ritual for Inducing Forgetfulness in Aeneid 4 - Silva, Gabriel A. F. (2021)
In this article, I examine the nature of Dido’s magic ritual in Aeneid 4, reading it as a magic ritual aimed at inducing forgetfulness. I argue that in burning his belongings, Dido intends to forget Aeneas and not to destroy him; for this purpose, I study this episode in the light of non-literary sources and of the poetic tradition concerning love magic and the obliteration of memory.